Metodologia de análise de risco de investimento em sistemas de geração distribuída a partir de biogás produzido em estações de tratamento anaeróbio de esgoto doméstico - Sestrem Junior, Jonas Abilio (2019)
Sanitation sector is electro-intensive and the energy recovery of biogas from anaerobic sewage treatment for distributed generation of electricity emerges as an alternative for the promotion of sustainability. In order to ensure prudent investments, it is necessary to support decision-making on the subject in technical-economic feasibility and risk analysis. In this context, this paper presents an innovative method capable of estimating the risk associated with investments in distributed electricity generation units from the recovery of biogas produced in anaerobic wastewater treatment plants (AWWTP). The method is probabilistic and combines the estimation of biogas production from AWWTP with the distributed generation of electricity through biogas conversion, the value at risk investment (VaR) and CVaR assessment (Conditional Value at Risk), sensitivity analysis as well as Monte Carlo simulation. A spreadsheet containing a transfer function was initially elaborated, enabling the convertion of the flow and COD data from the AWWTP into biogas and methane production rates. To that end it was utilized the method proposed by Lobato (2011) that considers all routes of COD convertion and losses in the anaerobic reactor. From methane production rates, it was estimated the amount of electricity that could be generated annually in a AWWTP, considering a motor generator group. The Monte Carlo simulation was then used to sample the input values of the transfer function and to simulate a representative distribution of methane production and the avoided electricity cost at the AWWTP from biogas conversion. Finally, these data were compared to the investment and operating costs (CAPEX) of the distributed electricity generation unit. Thus, a histogram with net present value (NPV) data was designed, and the investment risk was estimated using the VaR and CVaR analysis tools. The developed method was initially applied in a medium-sized WWTP located in Brazil. After consolidating the method, it was applied to three other similar AWWTPs . To this end, an yearly basis historical series of sewage flow and COD data arriving at the WWTP was processed. The results indicated that the distributed generation of electricity from biogas from these AWWTP has an acceptable risk margin, justifying the investment for three of them.